Fluorinated 3,6,9-trisubstituted acridine derivatives as DNA interacting agents and topoisomerase inhibitors with A549 antiproliferative activity - Nunhart, Patrik; Konkoľová, Eva; Janovec, Ladislav; Jendželovský, Rastislav; Vargová, Jana; Ševc, Juraj; Matejová, Mária; Miltáková, Beata; Fedoročko, Peter; Kozurkova, Mária (Bioorganic chemistry, 2020)
A series of new 3,6,9-trisubstituted acridine derivatives with fluorine substituents on phenyl ring were synthesized and their interaction with calf thymus DNA was investigated. Analysis using UV-Vis absorbance spectra provided valuable information about the formation of the acridine-DNA complex. In addition, compounds 8b and 8d were found to display an increased binding affinity (K = 2.32 and 2.28 × 106 M-1, respectively). Topo I/II inhibition mode assays were also performed, and the results verify that the novel compounds display topoisomerase I and II inhibitory activity; compounds 8a, 8b and 8c completely inhibited topoisomerase I activity at a concentration of 60 × 10-6 M, but only compound 8d showed partial ability to inhibit topoisomerase II at concentrations of 30 and 50 × 10-6 M. The ability of the derivatives to impair cell proliferation was tested through an analysis of cell cycle distribution, quantification of cell number, viability studies, metabolic activity measurement and clonogenic assay. The content and localization of the derivatives in cells were analyzed using flow cytometry and fluorescence microscopy. The compounds 8b and 8d altered the physiochemical properties and improved antiproliferative activity in A549 human lung carcinoma cells (compound 8d displayed the highest level of activity, 4.25 × 10-6 M, after 48 h).
Keywords: inhibitory topoisomerasy II; buňky A549; vztahy mezi strukturou a aktivitou; DNA-topoisomerasy typu II; Halogenation; Cell Proliferation; Humans; Structure-Activity Relationship; halogenace; skot; Molecular Structure; Topoisomerase II Inhibitors; Antineoplastic Agents; zvířata; protinádorové látky; Cattle; Acridines; Drug Screening Assays, Antitumor; Topoisomerase I Inhibitors; screeningové testy protinádorových léčiv; DNA Topoisomerases, Type II; akridiny; proliferace buněk; Dose-Response Relationship, Drug; DNA; Animals; vztah mezi dávkou a účinkem léčiva; lidé; A549 Cells; inhibitory topoisomerasy I; DNA-topoisomerasy I; DNA Topoisomerases, Type I; molekulární struktura